2016
DOI: 10.1038/srep26852
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide differential expression of genes and small RNAs in testis of two different porcine breeds and at two different ages

Abstract: Some documented evidences proved small RNAs (sRNA) and targeted genes are involved in mammalian testicular development and spermatogenesis. However, the detailed molecular regulation mechanisms of them remain largely unknown so far. In this study, we obtained a total of 10,716 mRNAs, 67 miRNAs and 16,953 piRNAs which were differentially expressed between LC and LW pig breeds or between the two sexual maturity stages. Of which, we identified 16 miRNAs and 28 targeted genes possibly related to spermatogenesis; 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 94 publications
(112 reference statements)
2
25
0
Order By: Relevance
“…In addition, after identifying the miRNA targets of each differentially regulated circRNA, we found that some candidate miRNAs targeted by several circRNAs are linked to mammalian development of sex differentiation and maturation. For example, miR-145-5p was found likewise up-regulated after sexual maturity in pigs (Li et al, 2016) and miR-214-3p was shown to be involved in the onset of mouse primordial germ and somatic cell sex differentiation (Fernández-Pérez et al, 2018). Those findings coupled to our results suggest that circRNAs probably regulate the onset of puberty.…”
Section: Discussionsupporting
confidence: 82%
“…In addition, after identifying the miRNA targets of each differentially regulated circRNA, we found that some candidate miRNAs targeted by several circRNAs are linked to mammalian development of sex differentiation and maturation. For example, miR-145-5p was found likewise up-regulated after sexual maturity in pigs (Li et al, 2016) and miR-214-3p was shown to be involved in the onset of mouse primordial germ and somatic cell sex differentiation (Fernández-Pérez et al, 2018). Those findings coupled to our results suggest that circRNAs probably regulate the onset of puberty.…”
Section: Discussionsupporting
confidence: 82%
“…However, hundreds of mature miRNAs have been detected in developing porcine testicular tissues. Therefore, further studies are needed to explore the functional roles of miRNAs in porcine Sertoli cells ( Luo et al, 2015 , 2018 ; Li et al, 2016 ; Xu et al, 2018 ). In the present study, we report that miR-222 inhibited cell cycle and proliferation and induced cell apoptosis in immature Sertoli cells by targeting the GRB10 gene through the inactivation of the PI3K/AKT signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…miR‐26a was widely identified in porcine testicular tissues using RNA‐seq technology (Li, Li, et al., ; Lian et al., ; Luo et al., ; Ran et al., ), suggesting its key roles in swine testicular development and spermatogenesis. Although previous studies reported that miR‐26a plays multiple regulatory roles in cell metabolic processes, including differentiation (Su et al., ), proliferation (Zhou et al., ) and apoptosis (Zhang et al., ).…”
Section: Discussionmentioning
confidence: 99%